METHODOLOGY FOR DEVELOPING MEDIA COMPETENCE IN FUTURE TEACHERS - Yuldashov Sherzod Sattorovich (Modern American Journals, 2025)
This article examines the impact of modern information technologies on the educational process and discusses the formation of future teachers’ media competence. It highlights the main components of media competence—information literacy, technological literacy, critical thinking, media product creation, as well as legal and ethical skills. Drawing on the theoretical perspectives of UNESCO, G. Gerbner, and J. Potter, the authors emphasize the importance of media competence in making the learning process more effective and interactive. Furthermore, they demonstrate the significance of an integrated approach to developing media competence, including practical exercises, interactive platforms, project-based learning, and gamification.
Keywords: Media competence, information literacy, technological literacy, critical thinking, media technologies, interactive learning, gamification, project-based learning.